The Executorial Role of the Administrative Court in Controlling Abuse and Restoring Trust - Herlambang, Pratama Herry; Ramadhani, Suci; Chandra, Felisha (Semarang State University Undergraduate Law and Society Review, 2025)
This article examines the role of the Administrative Court (PTUN) in judicial control over abuse of power (abusus potestatis) by administrative officials and its contribution to restoring public trust. Guided by Montesquieu’s separation of powers and A.V. Dicey’s rule of law, PTUN acts as a mechanism to correct administrative excesses. However, abuse of power remains prevalent in Indonesia. The PTUN’s execution mechanism, including dwangsom (coercive fines), is vital in enforcing rulings. Despite the legal framework under Undang-Undang Nomor 5 Tahun 1986 dan Undang-Undang Nomor 51 Tahun 2009 PTUN faces challenges in enforcement due to resistance from officials and inadequate measures. This article explores how PTUN can improve its role by strengthening its execution mechanisms and institutional support. Using normative legal research, the study analyzes relevant laws and jurisprudence to evaluate the effectiveness of PTUN’s execution process and propose reforms to enhance its ability to protect citizens’ rights and restore public trust.